Galactic Structure: A Constructivist Approach to Teaching Astronomy - Domenech, Antonio; Casasus, Elena (School science review, 1991)
An astrophysics course based on the constructivist approach to science teaching is described. The study of galactic structure is given as an example. Direct experiences and observations, representative-symbolic language, organized knowledge, and formal strategies are emphasized. (KR)